Catastrophic Health Expenditures With Pregnancy and Delivery in the United States - Peterson, Jessica A; Albright, Benjamin B; Moss, Haley A; Bianco, Angela (Obstetrics and gynecology (New York. 1953), 2022)
To describe prevalence, trends, and risk factors for catastrophic health expenditures in the year of delivery among birth parents (delivering people). We conducted a retrospective, cross-sectional study of the Medical Expenditure Panel Survey from 2008-2016. We identified newborn birth parents and a 2:1 nearest-neighbor propensity-matched control cohort of nonpregnant reproductive-aged individuals, then assessed for catastrophic health expenditures (spending greater than 10% of family income) in the delivery year. We applied survey weights to extrapolate to the noninstitutionalized U.S. population and used the adjusted Wald test for significance testing. We compared risk of catastrophic health expenditures between birth parents and the control cohort and described time trends and risk factors for catastrophic spending with subgroup comparisons. We analyzed 4,056 birth parents and 7,996 reproductive-aged females without pregnancy in a given year. Birth parents reported higher rates of unemployment (52.6% vs 46.6%, P<.001), and high rates of gaining (22.4%) and losing (25.6%) Medicaid in the delivery year. Birth parents were at higher risk of catastrophic health expenditures (excluding premiums: 9.2% vs 6.8%, odds ratio [OR] 1.95, 95% CI 1.61-2.34; including premiums: 21.3% vs 18.4%, OR 1.53, 95% CI 1.32-1.82). Birth parents living on low incomes had the highest risk of catastrophic health expenditures (18.8% vs 0.7% excluding premiums for 138% or less vs greater than 400% of the federal poverty level, relative risk [RR] 26.9; 29.8% vs 5.9% including premiums, RR 5.1). For birth parents living at low incomes, public insurance was associated with lower risks of catastrophic health expenditures than private insurance, particularly when including premium spending (incomes 138% of the federal poverty level or lower: 18.8% public vs 67.9% private, RR 0.28; incomes 139-250% of the federal poverty level: 6.5% public vs 41.1% private, RR 0.16). The risk of catastrophic spending for birth parents did not change significantly over time from before to after Affordable Care Act implementation. Pregnancy and delivery are associated with increased risk of catastrophic health expenditures in the delivery year. Medicaid and public coverage were more protective from high out-of-pocket costs than private insurance, particularly among low-income families.